Effectiveness of a simulation-based training for health professionals conducting evaluations of alleged torture and ill-treatment. (November 2020) - Moreno, Alejandro; Hor, Albert; Valencia, Victoria; Iacopino, Vincent
Abstract: Simulation has been used as an effective pedagogical tool for complex, high risk industries, including aviation, merchant marine, military, nuclear energy, and healthcare. Forensic science has also employed a variety of simulation training formats, such as virtual reality simulators, cadaver farms, objective structured clinical exercises, and mock trials. An evaluation of an alleged torture and ill-treatment victim is one of the most challenging types of evaluations forensic experts may conduct given the complex nature of the abuse and its physical and psychological effect, the status of perpetrators being State Officials, and the critical importance of judicial outcomes for alleged victims. The study presents a simulation-based training curriculum on the effective evaluation of alleged torture and ill treatment according to United Nations standards contained in the Istanbul Protocol and its effectiveness as measured by the participants' perceived gains in knowledge and skills. Of 262 participants, 176 pre-training surveys and 150 post-training surveys were collected for a response rate of 67% and 57%, respectively. Of the 899 end of day course evaluations distributed to the participants, 594 were returned for a response rate of 66%. Participants reported that the course increased their confidence to perform all aspects of the medico-legal evaluation of an alleged victim torture and ill-treatment. Participants' median score for the course content, instructors and course material was 5 using a 5-point Likert scale. The findings of this study demonstrate that a simulation-based course significantly improved the cognitive and technical skills necessary to conduct medico-legal evaluations of alleged victims of torture and ill-treatment in accordance with Istanbul Protocol standards. Highlights: A simulation-based training increased history-taking skills of torture evaluations. A simulation-based training increased examination skills of torture evaluations. Standardized patients may become traumatized during simulation-based trainings. Simulation is an effective pedagogical tool to teach human rights evaluations.